Influence of demographic factor on housing projects - Tytok, V.; Emelianova, O. (Ways to Improve Construction Efficiency, 2022)
Demographic processes and phenomena occurring in Ukraine can only be guessed at, as the last census in Ukraine was conducted in 2001. According to the State Statistics Service, as of September 1, 2021, the population of Ukraine was 41,342.5 thousand people. According to UN forecasts, by 2050 the population of Ukraine may decrease to 35 million people. The solution of key socio-economic problems of the state depends on the demographic situation in Ukraine. This includes the development of vast territories, and greater involvement in the economic circulation of natural resources and preserving the territorial integrity and security of the country. Demographic management at the regional level is becoming increasingly important today. One of the tools to improve demographic factors is housing construction, namely the formation of a market for quality and affordable housing. But we must not forget about the feedback, the impact of socio-demographic factors on the choice of living conditions. Changing the age limit for people of retirement age is of great social and political importance. In parallel with changes in population, the country is urbanizing - an increase in the share of urban population, which affects its consumer demands and preferences. We also began to spend more and more time with our family, so there was a need to allocate their own space for each family member: someone – a place for distance work, for children and students – a place for online learning, and do not forget about a safe place to relax or meet friends. Therefore, now one of the main priorities when choosing housing is comfort for the whole family. Also, the main characteristics when choosing housing should include the level of income (wealth) of the population. The aim of the article is to identify the relationship between age and population type. The analysis of the material condition of the population is carried out. The influence of human needs on the choice of housing type is estimated. Evidence of the possible relationship between age and demographics has been selected, as well as some explanations for the rationality of these preferences. The article uses research methods: analysis, synthesis, comparison, induction, deduction - to generalize and clarify the understanding of the demographic impact on housing choices by the population.